Implementation of Law Number 16 of 2011 Concerning Legal Aid as a Form of Implementation of the Welfare Law State Concept - Huda, Muhammad Wahyu Saiful; Astrovanapoe, Syahlila Umaya; Amalia, Tia; Latifiani, Dian (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2023)
The law that regulates all lines of life is included in regulating legal aid. Indonesia as a rule of law country certainly regulates the implementation of legal aid. However, in practice, legal aid in Indonesia is considered not to have run optimally because many people find it difficult to get legal assistance when they experience problems related to law from a civil-criminal perspective as well as state administration. This of course causes misery to the community and it can be judged that the community does not experience prosperity. Therefore, the author wants to examine this problem using normative juridical research methods. And found that there are problems juridically from Law Number 16 of 2011 Concerning Legal Aid, the community, and executors providing legal aid. especially oversight of funds for the provision of legal aid. Therefore it is necessary to change from a juridical and implementation perspective to be regulated again in order to meet the needs of the Indonesian people.